POLITIK UANG DALAM PEMILIHAN LEGISLATIF DI KOTA PEKANBARU TAHUN 2014 - Ariandi Saputra Saputra; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
In the legislative elections in the city of pekanbaru 2014 occurred several-fraund in the election among which the politics of money that will be undertaken by a number of candidates and the team sucses,where the practice of money politics is already affirmed in the election law of the republic of Indonesia under law No.8 of 2012 on General Election of members of parliament,local council and regional parliemens, chapter 8 of article 86 paragraph(1)”promising or giving money or other materials to the participants of the election campaign”therefore, the research is done in order to determine factors that cause and effect of money politics is to again avoice in the selections of candidates in the city legislatife pekanbaru 2014.This type qualitative research using descriptive method and research sites in the city pekanbaru.informan of this study consisted of the chairman of the cammission, the election supervisory committee, the candidates and public figures with data collection through direct interviews and documentation.The result showed that the pattern of money politics in the form of(1)the time(timing) that is on the campaign trail,the quide period and dawn raid.(2)the nature and from of the politics money(money and goods,repairs directly).and the factors that lead to money politics in the elections legislatife in town pekanbaru 2014 are:(1) the ambitions of candidates,(2)economic,(3)culture(4)regulatory supervision(5)socialization and political education to the society,(6)public confidence in the candidates. The impact of political money to the vote candidates are(1) the vote increased,meaning that money politics managed to improve the sound and was elected as a member of parliament,(2) The vote is note increased,meaning that money politics was not successful in creasing the voice that failed to become legislator pekanbaru 2014Keyword : Money Politic, Legislativ vote